The reasons behind Constitutio Antoniniana and its effects on the Roman military - Rocco, Marco (Acta Classica Universitatis Scientiarum Debreceniensis, 2020)
Reconsidering the contemporary sources concerning the constitutio Antoniniana, it can be argued that the edict of 212 AD disguised aims primarily connected to the needs of empire’s defence system. Caracalla intended at first place to increase state revenue earmarked for the army, and secondly to solve the recurring crises in the recruitment of Roman citizens joining the legions, by extending the pool for legionary enlistment to the empire’s entire territory. The new citizens surely felt the hardships of being legionnaires less than did the citizens of long date, who, on the other hand, could continue to prefer service in the auxilia. At the same time, the clause excluding dediticii from Roman citizenship was meant to safeguard the long ingrained practice of enlisting corps of specialists from subjected populations, which in the course of time would become elite units.